Motor proficiency as a predictor of physical activity and sedentary behavior in young adults: Insights from accelerometer-derived and self-reported measures - Jane Jie Yu; Ting-zhou Jin; Jia Yi Chow (Journal of Exercise Science & Fitness, 2025)
Objectives: To determine the associations of motor proficiency (MP) with physical activity (PA) and sedentary behavior (SB) in young adults who are facing elevated risks of physical inactivity and underdeveloped motor competence nowadays. Methods: Using a cross-sectional design, 103 university students aged 18–21 years were recruited in China for this study. MP was assessed using the Bruininks-Oseretsky Test of Motor Proficiency (2nd Edition). The time spent in PA (light PA [LPA] and moderate-to-vigorous PA [MVPA]) and SB were measured using both ActiGraph GT3X + accelerometers (worn for 7 consecutive days) and the Chinese version of the International Physical Activity Questionnaire-Short Form. PA and SB were compared by different MP levels (i.e., below average [MP-below] and at or above average [MP-above]) and gender. The associations of MP with accelerometer-derived and self-reported PA and SB outcomes and the agreement between the two measures were further ascertained. Results: Out of the 100 participants with valid data for analyses (73 females, 27 males; mean aged 19.76 ± 1.06 years), the MP-above group engaged significantly more in PA and less in SB than the MP-below group. Males performed significantly better than females on MP and spent less time on LPA (both p < .05). After adjusting for confounders, MP was a significant predictor of both total PA (p < .05) and sedentary time (p < .05) regardless of measurement modalities. Conclusions: MP is an independent predictor of PA and SB in university students, with males performing better in MP than their female peers. Developing effective and tailored programs that improve MP is important when promoting PA and health among young adults, particularly those with poor MP and females.